Complement Components Showed a Time-Dependent Local Expression Pattern in Constant and Acute White Light-Induced Photoreceptor Damage - Schäfer, Nicole; Grosche, Antje; Schmitt, Sabrina I.; Braunger, Barbara M.; Pauly, Diana (Frontiers in Molecular Neuroscience, 2017)
Background: Photoreceptor cell death due to extensive light exposure and induced oxidative-stress are associated with retinal degeneration. A correlated dysregulation of the complement system amplifies the damaging effects, but the local and time-dependent progression of this mechanism is not thoroughly understood. Methods: Light-induced photoreceptor damage (LD) was induced in Balb/c mice with white light illumination either for 24 h with 1000 lux (constant model) or 0.5 h with 5000 lux (acute model). Complement protein and mRNA expression levels were compared at 1 d and 3 d post LD for C1s, complement factor B (CFB), mannose binding lectin A (MBL-A), mannose-binding protein-associated serine protease 1 (MASP-1), C3, C4, C9 and complement factor P (CFP) in retina and RPE/choroid. Histological analyses visualized apoptosis, microglia/macrophage migration, gliosis and deposition of the complement activation marker C3d. Systemic anaphylatoxin serum concentrations were determined using an ELISA. Results: Apoptosis, gliosis and microglia/macrophage migration into the outer nuclear layer showed similar patterns in both models. Local complement factor expression revealed an early upregulation of complement factor mRNA in the acute and constant light regimen at 1 d post treatment for c1s, cfb, masp-1, c3, c4 and c9 in the RPE/choroid. However, intraretinal complement mRNA expression for c1s, cfb, c3 and c4 was increased at 1 d in the constant and at 3 d in the acute model. A corresponding regulation on protein level in the retina following both LD models was observed for C3, which was upregulated at 1 d and correlated with increased C3d staining in the ganglion cell layer and at the RPE. In the RPE/choroid C1s-complex protein detection was increased at 3 d after LD irrespectively of the light intensities used. Conclusions: LD in mouse eyes is correlated with local complement activity. The time-dependent local progression of complement regulation on mRNA and protein levels were equivalent in the acute and constant LD model, except for the intraretinal, time-dependent mRNA expression. Knowing the relative time courses of local complement expression and cellular activity can help to elucidate novel therapeutic options in retinal degeneration indicating at which time point of disease complement has to be rebalanced.